1999
DOI: 10.1164/ajrccm.160.1.9901063
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Relative Efficacy of Formoterol and Salmeterol in Asthmatic Patients

Abstract: Studies performed on airway smooth muscle in vitro have indicated that salmeterol is a partial agonist on the beta2-receptor in comparison to formoterol. In the present study we evaluated whether these pharmacological differences between salmeterol and formoterol also are applicable to asthmatic patients. The protective effects by increasing cumulative doses of formoterol (12, 60, 120 micrograms) and salmeterol (50, 250, 500 micrograms) on methacholine-induced bronchoconstriction were evaluated in a double-bli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
95
2
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(106 citation statements)
references
References 28 publications
6
95
2
3
Order By: Relevance
“…In addition, not all patients enrolled in the NJH study exhibited a clear dose-dependent decrease in the eNO levels (data not shown). Similar results were observed for approved doses of SX (50 mcg salmeterol for DPIs and 42 mcg salmeterol f o r p M D I s ) , u s i n g e i t h e r b r o n c h o d i l a t a t i o n o r bronchoprovocation PD model [20,21]. As a result, for the inhalation product containing an ICS and/or a LABA, a CE study should be used to support bioequivalence as part of the weight-of-evidence approach.…”
Section: Us Approach To Pharmacodynamic or Clinical Endpoint Studiessupporting
confidence: 77%
“…In addition, not all patients enrolled in the NJH study exhibited a clear dose-dependent decrease in the eNO levels (data not shown). Similar results were observed for approved doses of SX (50 mcg salmeterol for DPIs and 42 mcg salmeterol f o r p M D I s ) , u s i n g e i t h e r b r o n c h o d i l a t a t i o n o r bronchoprovocation PD model [20,21]. As a result, for the inhalation product containing an ICS and/or a LABA, a CE study should be used to support bioequivalence as part of the weight-of-evidence approach.…”
Section: Us Approach To Pharmacodynamic or Clinical Endpoint Studiessupporting
confidence: 77%
“…The rapid and sustained effects of formoterol on bronchodilation/bronchoprotection are well documented and have been mentioned earlier in this review (39,40). Other positive effects reported with LABAs include a reduction in the airway oedema that can occur during an asthma exacerbation by relaxing the endothelial cells (72), inhibition of the release of bronchoconstrictors, such as histamines, from mast cells (73) and beneficial effects on neutrophilic inflammation (23) (Fig.…”
Section: Safety Of Budesonide/formoterol Maintenance and Reliever Thementioning
confidence: 74%
“…The onset of action is not sufficient to provide immediate relief. Moreover, the partial agonist properties limit the benefit of increasing the dose above 100 lg/day (39,41). In a study involving a methacholine challenge, increasing the dose of salmeterol did not lead to enhanced bronchoprotection, in contrast to the added protection observed with increased doses of formoterol (39).…”
Section: Formoterol As a Fast-acting Relievermentioning
confidence: 99%
See 1 more Smart Citation
“…In clinical practice, however, there is no evidence suggesting that formoterol is more effective than salmeterol. A randomized double blind study performed in patients with asthma has shown that high dose formoterol provided better protection against metacholine-induced bronchoconstriction compared to salmeterol (20,21).…”
Section: History Of Labasmentioning
confidence: 99%